The formal composition of puns in Shakespeare’s "Love’s Labour’s Lost": A corpus-based study - Adamczyk, Magdalena (Adam Mickiewicz University, 2006)
The present paper is a corpus-based study seeking to demonstrate, both qualitatively and quantitatively, the formal composition of puns in one of Shakespeare’s early festive comedies, i.e. Love’s labour’s lost (c1593/4). Pun is defined here after Delabastita (1993: 57) as a phenomenon depending for its existence on the juxtaposition of (at least two) similar/identical forms and (at least two) dissimilar meanings, where, broadly speaking, the subtler the formal contrast and the sharper the semantic one, the finer the punning effect. The reason behind selecting this particular play for the examination has been the initial assumption that, rich in verbal experiments of all sorts, it might prove a fertile source of punning forms which, indeed, run altogether to 423 instances. The qualitative study is essentially two-partite and, initially, sets out to investigate linguistic phenomena which lay down the framework of formal relationships in a pun (and are, thus, in a mutually exclusive way, obligatory for its creation), namely homonymy, homophony and paronymy. Next, punning forms are grouped into interlingual puns, proper name puns as well as idiom- and compound- based puns. On top of that, a quantitative analysis is carried out which demonstrates (in a tabular and graphic form) the overall numerical and percentage distribution of all categories of puns established in the present research study.